2017
DOI: 10.1007/s10482-017-0977-5
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of avocado rhizobacteria against Fusarium euwallaceae and Graphium spp., associated with Euwallacea spp. nr. fornicatus, and Phytophthora cinnamomi

Abstract: Plant rhizobacteria have been successfully used as biocontrol agents against fungal phytopathogens. However, their potential to control two important avocado diseases, namely Fusarium dieback (FD) and Phytophthora root rot (PRR), has been poorly studied. FD is an emerging disease triggered by fungi associated with two ambrosia beetle species (Euwallacea fornicatus species complex), while PRR is caused by Phytophthora cinnamomi, a soil-borne oomycete. In the present work, the antifungal activity of bacteria iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 34 publications
0
37
1
Order By: Relevance
“…Rhizobacteria have proved to be a source of biological control agents of fungal phytopathogens in numerous studies [ 16 , 31 , 43 , 45 ]. In the present work, we found that isolate A8a, a phylogenetically close relative to Bacillus acidiceler , presented strong antagonism against P .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rhizobacteria have proved to be a source of biological control agents of fungal phytopathogens in numerous studies [ 16 , 31 , 43 , 45 ]. In the present work, we found that isolate A8a, a phylogenetically close relative to Bacillus acidiceler , presented strong antagonism against P .…”
Section: Discussionmentioning
confidence: 99%
“…cinnamomi , through the emission of both diffusible and volatile compounds ( Table 2 , Fig 5 and Fig 6 ). Species of the bacterial genus Bacillus have shown to inhibit the mycelial growth of several fungal pathogens, such as Fusarium euwallaceae [ 16 , 46 ], F . oxysporum and Rosellinia necatrix [ 15 ] and Phytophthora spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the importance of avocado around the world, there are just a few studies regarding its rhizosphere biology. Carzola et al [13] reported that four strains of Bacillus subtilis were associated with avocado antifungal activity and showed apparent enzymatic and antibiotic action against phytopathogenic fungi, whereas Guevara-Avendaño et al [14] identified Bacillus strains with the ability to control the phytopathogenic fungi Fusarium euwallaceae and Graphium sp. Méndez-Bravo et al [15] described the effects of Bacillus, Pseudomonas and Arthrobacter isolated from the avocado rhizosphere against Phytophthora cinnamomi through the production of volatile organic compounds.…”
Section: Introductionmentioning
confidence: 99%